Study on Sample Pretreatment of Sediments by High Temperature and High Pressure Digestion with Bomb - Zhang, Weina (Asian Journal of Chemistry, 2014)
A new fast pretreatment method for sediments which digested on high temperature and high pressure ambient in bomb was proposed. The influence of the weight of sample, the species and dosage of solvents, digested time and temperature on digestion ability of sediments were studied. The results showed that the digestion effect was best when the weight of sample was nearly 0.010 g, the solvent was 0.5 mL HCl + 1.5 mL HNO3, digested temperature and time were 160 °C and 6 h, respectively.